High-efficiency microdrilling of glass by parallel transient and selective laser processing with spatial light modulator. (October 2022) - Yoshizaki, Reina; Ito, Yusuke; Ogasawara, Kazuma; Shibata, Akihiro; Nagasawa, Ikuo; Sano, Tomokazu; Nagato, Keisuke; Sugita, Naohiko
Graphical abstract: Highlights: The parallel transient and selective laser processing using the spatial light modulators is developed. The methods to combine the two lasers with a different wavelength controlled with each spatial modulator is reported. Two 100-µm depth 10-µm diameter holes are drilled in 50 µs with the parallel transient and selective laser processing. The processing condition in the parallel transient and selective laser processing is studied. Abstract: To use glass as the substrate material in next-generation large-scale integrations and biochips, the high-speed fabrication of high-aspect-ratio microholes is necessary. Transient and selective laser (TSL) processing significantly reduces the processing time per hole. To further improve the processing efficiency, parallel TSL processing using a spatial light modulator is proposed in this study. Two 100-µm depth holes are successfully machined in parallel, in 50 µs. Furthermore, the process control parameters are investigated through high-speed observation and the laser irradiation conditions required for processing are clarified. Parallel processing of three or more holes and depth control of each hole is expected to be realized in future.